The Vital Spaces of the Argentine South: The South Atlantic and the Future of Antarctica - Gioffreda, Camilo (2021)
This article analyzes the strategic scenario of the South West Atlantic as an area of current and potential conflicts that the Argentine Republic must face. In the first place, we address the influence of the great powers over this maritime space. In the second place, the role that the Island of the States can exercise as a platform of projection to Malvinas and Antarctica. Finally, we discuss future-oriented facts that point to a clear scenario of competition for the white continent in the coming decades. We present an analysis of descriptive and explanatory type, with a qualitative approach, based on the revision of bibliographic sources, official documents and journalistic articles. We conclude that Argentine is very far to maintain full sovereignty and a truly effective national territory over the map that the country presents and defines as bicontinental.